Vitamin C Inhibits Metastasis of Peritoneal Tumors By Preventing Spheroid Formation in ID8 Murine Epithelial Peritoneal Cancer Model - Xu, Yayun; Guo, Xing; Wang, Ganyu; Zhou, Changkuo (Frontiers in Pharmacology, 2020)
High mortality is associated with exclusively metastasis within the peritoneal cavity among patients with epithelial ovarian cancer that is the most lethal gynecologic cancer. There is an unmet need to develop more effective therapies to prevent metastasis of peritoneal cancer. Multicellular spheroid formation, during which cancer cells migrate and adhere to tumor-associated macrophages, is a critical step of ovarian cancer metastasis. Here, we showed that vitamin C inhibited spheroid formation and metastasis in ID8 ovarian cancer-bearing mice. We further found that vitamin C treatment decreased the levels of M2 macrophages in tumor nodules and suppressed the epithelial-mesenchymal transition (EMT). In vitro studies revealed that vitamin C inhibited proliferation, arrested cell cycle, attenuated migration, and prevented the spheroid formation of ID8 ovarian cancer cells. Vitamin C induced apoptosis of ID8 cells, which was confirmed by membrane potential collapse, cytosolic calcium overload, ATP depletion and caspase-3 activation in vitamin C-treated cells. Intriguingly, vitamin C treatment caused striking morphological change and apoptosis of macrophages. The presented proof of concept study strategically identifies new anticancer mechanisms of vitamin C.